Verification of IMRT and RapidArc Localized Prostate Cancer Treatment Plans Using EPID and Delta4 in vivo Dosimetry Methods - Moustafa Ahmed (Shiraz University of Medical Sciences, 2021)
Background: Quality assurance for intensity modulated radiation therapy (IMRT) depends on the type of dosimetry system and its evaluation procedure. We can check both the intensity and distribution of each field as the required pretreatment verification with dosimetry systems. Method: Treatment verification for different plans (IMRT and RapidArc) applied on localized prostate cancer patients was done with electronic portal imager device (EPID), Delta4). The EPID used was Varian aS1000 mounted on Varian (TrueBeam) Linac with gamma criteria set to ΔD=3% and Δd=3mm. RapidArc plans were designed by arcs (179.0o CCW to 181.0o and 181.0o CW to 179.0o) under the same gamma criteria of (ΔD=3%, DTA=3mm and Δ-index ≤1), while the threshold dose was 20%. Results: Evaluation analysis is passed for IMRT prostate plans with the area gamma 0.8 (was equal to 2.1%) / area gamma >1.2 (was equal to 0.3%) and the average dose difference was 0.42CU. Delta4 dosimetry system was assessed with RapidArc plan; the agreement between the measured and planned doses was ±1% and gamma analysis resulted in 100% data points with the same agreement conditions. Conclusion: Portal dosimetry provided a good verification of the treatment unit ability to deliver doses according to plan. For an IMRT field comprised of several subfields, it could give rise to much more errors. RapidArc plans were verified using Delta4 system, which generated excellent dosimetry results. Periodic calibration was recommended for Delta4 dosimetry system; radiation damage affected sensitivity by >1% every 1kGy.